SEASONAL DYNAMICS OF THE PRESENCE OF CULICOIDES SPP. IN SERBIA IN THE PERIOD 2015-2016 - Ivan Pavlović; Ljubiša Veljović; Vesna Milićević; Jelena Maksimović-Zorić; Slobodan Stanojević; Oliver Radanović; Boban Đurić; Budimir Plavšić; Ana Vasić (Archives of Veterinary Medicine, 2019)
Genus Culicoides spp. includes small insects 0.5-2 mm in length, usually grey or black and at first glance very similar to mosquitoes. They are strictly hematophagous, feeding by attacking hosts outdoors and indoors (although they are less susceptible to the stationing like Aedes mosquitoes do). The sting is very painful at the injection site and often followed by hypersensibilisation with the consequent formation of allergic dermatitis. In addition, the insects carry and transmit a multitude of diseases, often of a zoonotic character, and therefore are of great epidemiological importance. In our country, continuous monitoring of Culicolides spp. has been carried out and seasonal dynamics of their appearance in the period 2015-2016 is presented in this article. During October 2015, the presence of Culicolides spp. was confirmed in 10.00% of samples; in November, their presence was not established, whereas in December, 2.35% of samples proved positive for the presence of Culicolides spp. During 2016, from January to March, no Culicolides spp. were found in any of the examined samples. During April, their prevalence was 9.63%, in May - 6.74%, in June - 3.70%, in July - 15.78%, in August - 18.07%, in September - 27.27%, and in October - 45.65%. In Serbia, the dominant Culicoides spp. species are Obsoletus complex and Pulicaris complex established in 57.21% and 33.37% of samples, respectively. Other species are present in lesser extent. In Obsoletus complex, the dominant species was Culicoides obsoletus/scoticus. The percentage of Culicoides obsoletus /scoticus males in samples was 25.52%. Non-pigmented (young) females were present in 66.06% of samples; females who took blood in 7.55% and 0.87% were gravid females. In Pulicaris complex, the dominant species was Culicoides pulicaris. Males of Culicoides pulicaris were found in 19.23% of samples, non-pigmented (young) females in 70.96%, females who took blood in 9.08% while 0.73% were gravid females.